Pharmacokinetic similarity study comparing the biosimilar candidate, LY05008, with its reference product dulaglutide in healthy Chinese male subjects - Zhang, Qin; Sun, Cheng; Wu, Jinying; Wu, Juan; Zhang, Xuan; Liu, Yueyue; Dou, Changlin; Qin, Huilin; Zhang, Qian; Zhou, Renpeng; Hu, Wei (Expert opinion on biological therapy, 2023)
Dulaglutide, a glucagon-like peptide-1 (GLP-1) receptor agonist, has been approved for improving glycemic control and reducing the risk of cardiovascular (CV) adverse events. This study compared the pharmacokinetic (PK) profiles, safety, and immunogenicity of LY05008, a biosimilar candidate, to a licensed product dulaglutide in healthy Chinese male subjects. In this double-blind, open-label, parallel-group study, healthy Chinese male subjects were randomized 1:1 to receive either LY05008 or dulaglutide subcutaneously. Primary study endpoints were PK parameters such as the area under the concentration-time curve (AUC) from time zero to infinity (AUC ), AUC from time zero to the last quantifiable concentration (AUC ), and maximum serum concentration (C ). Safety and immunogenicity profiles were also included for data analysis. 82 subjects were randomized to receive LY05008 (n = 41) or dulaglutide (n = 41). The 90% confidence intervals (CIs) of the geometric mean ratios (GMRs) of AUC AUC and C of LY05008 to dulaglutide were all within the bioequivalence limits of 80%-125%. Other PK parameters, safety, and immunogenicity profiles were comparable across the two treatment groups. This study demonstrated PK similarity of LY05008, a dulaglutide biosimilar, to dulaglutide in healthy Chinese male subjects, with comparable safety and immunogenicity data. The trial is registered at the Chinese Clinical Trial Registry (Identifier No. ChiCTR2200066519).